Characterization of Microstructure Static Mixer Reactors: Transport Phenomnena and Calorimetry for Mixing Limiting Reactions - Adams, James (Université d'Ottawa / University of Ottawa, 2025)
The production of active pharmaceutical ingredients (APIs) is transitioning from conventional semi-batch processes towards continuous flow chemistry solutions. Continuous flow chemistry processes can be miniaturized and intensified to increase production quality and throughput. The smaller reactor volumes, in contrast to batchwise processes, have improved temperature control and diminish the risk and severity of accidents such as thermal runaways. Furthermore, continuous flow reactors can produce APIs that are ill-suited, difficult, or impossible to produce in conventional batchwise processes. Notably highly exothermic reactions at severe risk of thermal runaway, multiphase systems, and unstable products prone to decomposition or degradation. In this study, the transport phenomena (frictional pressure loss, heat transfer, and residence time distribution) of a continuous flow shell and tube reactor are characterized for good manufacturing practices (GMP) production. The reactor features Kenics® static mixers to enhance the transport phenomena. The operating conditions and transport parameters were investigated in a dimensionless manner via friction factor, Nusselt and Peclet numbers. Empirical correlations are generated for the friction factor and inner tube Nusselt numbers covering tube diameters of 3.05 mm, which have not been reported in literature. The correlations generated accurate fits of the experimental data in the range of hydraulic Reynolds numbers (200 < Reₕ < 4500) and Prandtl numbers (4.6 < Pr < 7.0). The residence time distribution (RTD) characterization found that the reactor is effectively plug flow as the Peclet number surpassed one hundred for the investigated power dissipations (0.15 W·kg⁻¹ < ε < 1.6 W·kg⁻¹). Furthermore, the heat of reaction for the synthesis of lithium diisopropylamine (LDA) from n-butyllithium (nBuLi) and diisopropylamine (DIPA) is estimated with a continuous calorimeter featuring a microstructure of static mixers. The LDA synthesis organolithium reaction is mixing limiting. The associated energy and species balance differential equations are solved with a MATLAB® simulation to obtain the heat of reaction. The heat of reaction is estimated to be between -132 kJ·kg⁻¹ and -148 kJ·kg⁻¹. The variation in the heat of reaction is presumed to occur from the significant variation in the local overall heat transfer coefficient along the reactor length. Suggesting that one or more thermal resistance undergoes substantial change. Of which the conductive resistances associated with the static mixer blade and thermocouple rod may be responsible.
Keywords: Flow Chemistry; Characterization; Calorimetry; Pharmaceutical Industry